Biblical story re-told at City of Bethlehem - Wesselhoeft, Conrad (Raton, NM Raton Range, 1981)
Newspaper article on the City of Bethlehem.
Master list item #: 31
File location is in the Raton file Cabinet
Keywords: Gurule, Bob; Stoller, Bob; Lackey, John; Lincoln, Abe; Lions Club; Raton City Manager; KRTN; Raton Public Service; Local History; Display History; Christmas Exhibits; Holiday Traditions; Drive Through Exhibits; Christmas Lights; City of Bethlehem; Climax Canyon; Apache Avenue; Raton, New Mexico